Optimal Deposition Conditions of TiN Barrier Layers for the Growth of Vertically Aligned Carbon Nanofibers - Rafieian, Damon (My University, 2010)
The synthesis of vertically aligned carbon nanofibers (VACNF) employing catalytic plasma enhanced chemical vapor deposition has rendered them a distinguished building block for the fabrication of nanoelectromechanical devices (NEMS). However, it is clear that the electrical properties of such a device are highly affected by the electrical properties of the underlying material. Nevertheless, the existing excellent candidates such as gold and copper must be isolated from the catalyst material by a diffusion barrier layer in order to hinder the interdiffusion while good electrical contact to the nanofibers is maintained. Being known as a good diffusion barrier with relatively low resistivity, TiN has been nominated to serve the purpose. On the other hand, depending on the deposition condition, the microstructure and resulting TiN properties varies to a large extent. In this work we have developed a novel method to deposit stoichiometric TiN using dc reactive magnetron sputtering and evaluated the diffusion barrier of the sputtered TiN film continuously by annealing them in a plasma enhanced chemical vapor deposition (PECVD) chamber. Furthermore, we have successfully minimized the resistivity of the sputtered TiN by modification of the sputtering conditions. We have employed an easy-to-implement, high throughput and inexpensive technique called colloidal lithography for patterning the Ni catalysts dots on top of the TiN substrates. The composition ratio and transition between the phases of sputtered TiN films have been characterized by X-ray photoelectron spectroscopy as well.
Keywords: Materialvetenskap; Nanovetenskap och nanoteknik; Elektrofysik; Övrig teknisk materialvetenskap; Materials Science; Nanoscience & Nanotechnology; Electrophysics; Other materials science